Suddenly the storm - Slabolepszy, Paul, 1948- (Wits University Press, 2017)
Combative, volatile, constantly on the verge of exploding, Dwayne and Shanell Combrink are two halves of a white South African working-class couple, living an uneasy truce as they struggle with the day-to-day trials of scraping together a living and dreaming competing dreams. But beneath Dwayne's angry, violent exterior lies the heartbreak that governs his attitude to life. Dwayne is a man in mourning. Shanell believes his current level of despair was sparked by the death of his childhood friend and recent work partner, Jonas, but the source of his mourning and anger lies much further back. When the elegant and self-contained Namhla Gumede, born on 16 June 1976, arrives on their doorstep seeking answers to questions that have remained buried for 40 years, Dwayne and Shanell finally find out the truth. What starts as a smouldering dark comedy suddenly turns into a roller-coaster ride of startling revelations, rage and recrimination ... before the storm finally breaks.